Understanding food security determinants and coping strategies among smallholder farming households in Northern Ethiopia - Misgina Gebrehiwot; Biadgilgn Demisse; Hailemariam Meaza; Tafesse W. Gezahegn; Aradom Gebrekidan Abbay; Sisay Beyene (Cogent Social Sciences, 2024)
Empirical information on food insecurity at the disaggregated geographic level is vital for effective interventions. Using a household survey, we explored the prevalence of food insecurity among smallholder farming households and analyzed the factors associated with it in northern Ethiopia. We collected data from 353 smallholder farmers and utilized the dietary intake method to assess and quantify food security. Nearly half (49.3%) of households are unable to meet the minimum energy requirement for a healthy and active life. The distribution of available calorie intake reveals that approximately 29% of farmers are precariously close to the food security line, indicating a state of vulnerability. While, factors such as education, social linkage, migration, number of livestock (mules) owned by households, access to drinking water, use of fertilizer, plain farmland and being a maize producer have positive and significant influences, large family size has negative and significant influence in smallholders’ food security status. The major coping strategies identified indicate the severity of food insecurity in the region and the resilience and adaptability of farming households in the face of food insecurity. The findings suggest the need for more sustainable solutions to address the root causes of food insecurity, such as improving agricultural productivity through high-quality crop varieties and agricultural technologies, enhanced access to education, financial and market services and strengthening social safety nets to improve food security among smallholder farmers in northern Ethiopia.